(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Vaginal birth after cesarean section (VBAC) is a vital option for women with a prior cesarean section (C/S), but its success depends on some maternal factors, obstetric history, and labor conditions. This study aimed to find out the potential risks and benefits of VBAC. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) (currently, Bangladesh Medical University), Dhaka, Bangladesh, from January 2023 to December 2024. This study included 162 pregnant women with a history of one C/S attending the Obstetrics and Gynaecology department of BSMMU. Results: Most of the participants (75.3%) were between 21–30 years old. Among the women who attempted TOLAC, 33.3% successfully had a VBAC, while 66.7% required an emergency repeat cesarean section. Fetal distress (51.3%) was the most common reason for the previous cesarean and the main cause of emergency repeat cesarean section after failed trial, which is 48.2%. Babies born through VBAC had satisfactory neonatal outcomes, with 90.7% having a good Apgar score (>7) compared to 75.9% in the emergency repeat caesarean section (ERCS) group. Conclusion: This study found that fetal distress is a major factor leading to ERCS and underscores the better neonatal outcomes and lower postpartum hemorrhage rates in VBAC deliveries.